Emerging Importance of Helicases in Plant Stress Tolerance: Characterization of Oryza sativa Repair Helicase XPB2 Promoter and Its Functional Validation in Tobacco under Multiple Stresses - Raikwar, Shailendra; Srivastava, Vineet K.; Gill, Sarvajeet S.; Tuteja, Renu; Tuteja, Narendra (Frontiers in Plant Science, 2015)
Genetic material always remains at the risk of spontaneous or induced damage which challenges the normal functioning of DNA molecule, thus, DNA repair is vital to protect the organisms against genetic damage. Helicases, the unique molecular motors, are emerged as prospective molecules to engineer stress tolerance in plants and are involved in nucleic acid metabolism including DNA repair. The repair helicase, XPB is an evolutionary conserved protein present in different organisms, including plants. Availability of few efficient promoters for gene expression in plants provoked us to study the promoter of XPB for better understanding of gene regulation under stress conditions. Here, we report the in silico analysis of novel stress inducible promoter of Oryza sativa XPB2 (OsXPB2). The in vivo validation of functionality/activity of OsXPB2 promoter under abiotic and hormonal stress conditions was performed by Agrobacterium-mediated transient assay in tobacco leaves using OsXPB2::GUS chimeric construct. The present research revealed that OsXPB2 promoter contains cis-elements accounting for various abiotic stresses (salt, dehydration, or cold) and hormone (Auxin, ABA, or MeJA) induced GUS expression/activity in the promoter-reporter assay. The promoter region of OsXPB2 contains CACG, GTAACG, CACGTG, CGTCA CCGCCGCGCT cis acting-elements which are reported to be salt, dehydration, cold, MeJA, or ABA responsive, respectively. Functional analysis was done by Agrobacterium-mediated transient assay using agroinfiltration in tobacco leaves, followed by GUS staining and fluorescence quantitative analyses. The results revealed high induction of GUS activity under multiple abiotic stresses as compared to mock treated control. The present findings suggest that OsXPB2 promoter is a multi-stress inducible promoter and has potential applications in sustainable crop production under abiotic stresses by regulating desirable pattern of gene expression.